E0354 Angiographic characteristics of premature coronary heart disease—analyses of single center. (17th November 2010) - Lijian, Gao; Jun, Chen; Jilin, Chen; Yuejin, Yang; Shubin, Qiao; Bo, Xu; Jianjun, Li; Xuewen, Qin; Jinqing, Yuan; Yongjian, Wu; Jue, Chen; Shijie, You; et al.
Abstract : Background: There are no large-sample published reports prospectively or consecutively assessing the angiographic characteristics of premature coronary heart disease in China. Objectives: The present study was carried out to collect and analyse the clinical and angiographic characteristics in a single center. Methods: From April 2004 to April 2008, based on the screening condition of male <55 years and female (<65 years), we selected premature coronary heart disease from a dedicated database of coronary angioplasty registry of the Center for Diagnosis & Treatment of Coronary Artery Disease, Fuwai Hospital. They had been subjected to coronary angiogram due to the angina pectoris or asymptomatic myocardial ischaemia in coronary heart disease. Results: 4478 consecutive patients (3056 males, 1422 females), average age was (49.9±7.0) years, were defined as coronary heart disease according to clinical manifestation and coronary angiogram. Patients with unstable angina pectoris (UAP), stable angina pectoris (SAP) and without angina pectoris were 2400, 1534 and 544, respectively. The proportion of coronary heart disease, hypertension, hyperlipidaemia, diabetic mellitus (DM), smoking history, prior myocardial infarction (MI), prior percutaneous intervention (PCI), coronary artery bypass graft and history of cerebrovascular diseases were 6.7%, 53.0%, 35.3%, 20.8%, 90.3%, 43.3%, 16.6%, 1.5%, 1.1%, respectively. The ratio of eccentric lesions, concentric lesions, chronic total occlusion lesions (CTO) and calcified lesions were 93.7%, 23% and 42.8%, respectively. Comparison between UAP and SAP, there was more MI, PCI, complex lesions (B2+C), eccentric lesions and calcium lesions among 3934 patients. There were more MI, PCI, DM, hyperlipidaemia, hypertension, cerebrovascular diseases, smoking, eccentric lesions complex lesions, angulated lesions and calcified lesions in male than that in female (all p<0.05). Conclusions: The ratio of sex and clinical findings are different in Chinese Premature coronary heart patients. There were more MI, PCI, complex lesions, eccentric lesions and calcified lesions in UAP group, comparison between sexes, there were higher incidences of hypertension, hyperlipidaemia, cerebrovascular disease and smoking history in male.